2015
DOI: 10.1101/034785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel enrichment strategy reveals unprecedented number of novel transcription start sites at single base resolution in a model prokaryote and the gut microbiome

Abstract: Background: The initiating nucleotide found at the 5' end of primary transcripts has a distinctive triphosphorylated end that distinguishes these transcripts from all other RNA species. Recognizing this distinction is key to deconvoluting the primary transcriptome from the plethora of processed transcripts that confound analysis of the transcriptome. The currently available methods do not use targeted enrichment for the 5′end of primary transcripts, but rather attempt to deplete non-targeted RNA.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(86 citation statements)
references
References 28 publications
2
84
0
Order By: Relevance
“…We tested the ToNER tool for annotating transcript 5′ ends using Cappable-seq data [4]. The program output of frequency distributions of the number of mapped read starts per position of the two compared libraries reveal a lower complexity of enriched libraries, which are largely consistent with the effective enrichment of RNA 5′ end fragments employed in this method (S1 Fig).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…We tested the ToNER tool for annotating transcript 5′ ends using Cappable-seq data [4]. The program output of frequency distributions of the number of mapped read starts per position of the two compared libraries reveal a lower complexity of enriched libraries, which are largely consistent with the effective enrichment of RNA 5′ end fragments employed in this method (S1 Fig).…”
Section: Resultsmentioning
confidence: 75%
“…tRNA are also resistant to exonuclease. Recently, the Cappable-seq method was described as an alternative transcript 5′ end mapping technique, which employs a more efficient enrichment method [4]. In Cappable-seq, a biotinylated guanosine cap is added specifically to the 5′ triphosphate end of mRNA using vaccinia virus capping enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some of those methods rely on the same biochemical approaches as those developed for radioactive labeling. For example, it has been recently reported that VCE apart from GTP accepts certain GTP analogs as substrates, including those functionalized at the ribose moiety [67][68][69]. Taking advantage of this, VCE has been independently used to transfer a biotinylated [69] or anthraniloylated [68] GMP moiety to the 5 0 end of RNA from a GTP analog appropriately functionalized at the ribose moiety.…”
Section: Enzymatic Labeling Beyond Radioactive Phosphatesmentioning
confidence: 99%
“…For example, it has been recently reported that VCE apart from GTP accepts certain GTP analogs as substrates, including those functionalized at the ribose moiety [67][68][69]. Taking advantage of this, VCE has been independently used to transfer a biotinylated [69] or anthraniloylated [68] GMP moiety to the 5 0 end of RNA from a GTP analog appropriately functionalized at the ribose moiety. Notably, the label structure is of great importance for success in this approach, since a similar reaction using GTP carrying a manthraniloyl dye failed to produce capped transcripts [68].…”
Section: Enzymatic Labeling Beyond Radioactive Phosphatesmentioning
confidence: 99%